From national exceptionalism to national imperialism: changing motives of comparative education. Issue 3 (4th May 2022) - Tröhler, Daniel
ABSTRACT: The guiding thesis of this article is that international comparisons have been shaped by nationalist, and thus potentially imperial, religious and consequently also latent missionary, motives. By means of selected milestones in the last 250 years, this thesis is made plausible by asserting a historical development of nationalism that started from an almost defiant national self-determination in the eighteenth century, leading to learning from strangers in the long nineteenth century, and resulting in the imperially minded instruction of others in the course of the twentieth century.